Penyelesaian Sengketa Hak Atas Tanah Antara Pemerintah dengan Masyarakat di Sepanjang Jalan Gatot Subroto Kota Dumai - Husna, Irdatul; Hasanah, Ulfia; Lestari, Rika (Peneliti.net, 2024)
Acquisition of land rights can only be obtained through registration of land rights with the BPN, as the state institution authorized to issue land rights certificates. Then based on the provisions in the UUPA, for foreign companies that have representatives in Indonesia can only have the Right of Use as a form of ownership of land rights. Thus, the research objectives of this Researcher's thesis are first how the status of land rights along Jalan Gatot Subroto Dumai City and second how the settlement of land rights disputes between the government and the community along Jalan Gatot Subroto Dumai City. The type of legal research used is sociological juridical legal research, with research locations in Bangsal Aceh Village and Mekar Sari Village. The population and samples in this study are the parties related to the problem under study. This research uses primary data sources and secondary data and data collection techniques are carried out by means of interviews and studies. From the results of the research, the status of the land/land concession of PT. CPI is still unclear because the maintenance of land registration data cannot be carried out. Therefore, whatever dispute resolution efforts the parties choose in resolving land disputes, in this case mediation, the mediator must be neutral to be able to produce fair agreements for the parties.